Recovery of State Losses from Corruption Proceeds - Dannie Chaeruddin; Zainal Arifin Hoesein (Cognitionis Civitatis et Politicae, 2024)
Corruption cases in Indonesia have become a focal point of public concern, involving individuals from diverse professional backgrounds, including judges, prosecutors, police officers, legislators, and businesspeople. These crimes result in significant financial losses for the state. The urgency of establishing an effective mechanism to recover state losses from corruption has become increasingly apparent. This study aims to explore the mechanisms and strategies necessary for the recovery of state losses resulting from corruption, whether committed by individuals or corporations. Utilizing a qualitative research method with a focus on legal and economic analysis, the study examines current practices and their effectiveness in recovering state assets. The findings indicate that existing mechanisms only recover 10-15 percent of the total corrupted funds, highlighting significant inefficiencies in the system. The study concludes that comprehensive reforms, including the strengthening of legal frameworks, enhanced inter-agency collaboration, and public awareness, are imperative to improve recovery rates and deter corruption. Addressing these issues is essential to safeguarding public funds and restoring trust in the legal system.